Manufacturing Operations in Europe: Where Do We Go Next? - De Meyer, Arnoud (Institutional Knowledge at Singapore Management University, 1998)
Extrapolating from the results of a 10-year INSEAD Survey, the author offers some views on the future for manufacturing in Europe. The model on which the Survey was based indicates that competitive priorities and action plans in manufacturing changed over the 10-year period. Taking lessons from these, the author makes some 'informed guesses' on the future implications for European manufacturers in the form of seven normative features: innovation in the value package; close integration between manufacturing and service; the importance of internationalism; flexible project-based organisation; more integrated management of the value added chain; successful transformation of operational programmes into strategic programmes; and building a knowledge-based organisation.